2022
DOI: 10.3390/polym14153065
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength Estimation of Steel-Fiber-Reinforced Concrete and Raw Material Interactions Using Advanced Algorithms

Abstract: Steel-fiber-reinforced concrete (SFRC) has been introduced as an effective alternative to conventional concrete in the construction sector. The incorporation of steel fibers into concrete provides a bridging mechanism to arrest cracks, improve the post-cracking behavior of concrete, and transfer stresses in concrete. Artificial intelligence (AI) approaches are in use nowadays to predict concrete properties to conserve time and money in the construction industry. Accordingly, this study aims to apply advanced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Al-Abdaly et al 50 also reported that RF (R 2 = 0.88, RMSE = 5.66, MAE = 3.8) performed better than MLR (R 2 = 0.64, RMSE = 8.68, MAE = 5.66) in predicting the CS of SFRC. Khan et al 55 also reported that RF (R 2 = 0.96, RMSE = 3.1) showed more acceptable outcomes than XGB and GB with, an R 2 of 0.9 and 0.95 in the prediction CS of SFRC, respectively. Moreover, Nguyen-Sy et al 56 and Rathakrishnan et al 57 , after implementing the XGB, noted that the XGB was the best model for predicting the CS of NC.…”
Section: Resultsmentioning
confidence: 95%
“…Al-Abdaly et al 50 also reported that RF (R 2 = 0.88, RMSE = 5.66, MAE = 3.8) performed better than MLR (R 2 = 0.64, RMSE = 8.68, MAE = 5.66) in predicting the CS of SFRC. Khan et al 55 also reported that RF (R 2 = 0.96, RMSE = 3.1) showed more acceptable outcomes than XGB and GB with, an R 2 of 0.9 and 0.95 in the prediction CS of SFRC, respectively. Moreover, Nguyen-Sy et al 56 and Rathakrishnan et al 57 , after implementing the XGB, noted that the XGB was the best model for predicting the CS of NC.…”
Section: Resultsmentioning
confidence: 95%
“…In practice, these ML techniques are typically employed to approximate outputs from given inputs (YUAN et al, 2022). ML techniques are being employed to predict the strength, durability, and temperature resistance of materials (AMIN et al, 2022;KHAN et al, 2022C). Nevertheless, there are some limitations associated with the use of ML methods.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of precision medicine's rapid evolution, machine learning (ML) techniques are becoming progressively prevalent in medical imaging analysis and treatment planning [12]. ML's approach, not requiring prede ned relationships between input and output variables [13], offers a more adaptable and comprehensive analysis framework. This method effectively considers all interactions and potential modi cations of effects among these variables.…”
Section: Introductionmentioning
confidence: 99%